2021
DOI: 10.3201/eid2702.203517
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Timing of Initial Virus Shedding in Severe Acute Respiratory Syndrome Coronavirus 2, Utah, USA

Abstract: Virus shedding in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can occur before onset of symptoms; less is known about symptom progression or infectiousness associated with initiation of viral shedding. We investigated household transmission in 5 households with daily specimen collection for 5 consecutive days starting a median of 4 days after symptom onset in index patients. Seven contacts across 2 households implementing no precautionary measures were infected. Of these 7, 2 tested positive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 14 publications
6
24
0
1
Order By: Relevance
“…Indeed, a previous study showed no difference in the rate of SARS-CoV-2 contaminated surfaces in rooms occupied by symptomatic and asymptomatic persons at the time of environmental sampling [13]. Our data are consistent with studies showing that viral shedding from persons infected with SARS-CoV-2 peaks early in the course of infection [25,26] and that environmental contamination with SARS-CoV-2 is more likely when patient viral loads are at their highest [1]. Taken together, our data suggest that surface contamination with SARS-CoV-2 occurred through direct contamination with respiratory fluids following close, prolonged contact with sick persons early in their course of illness, particularly in the case of pillows and nightstands.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, a previous study showed no difference in the rate of SARS-CoV-2 contaminated surfaces in rooms occupied by symptomatic and asymptomatic persons at the time of environmental sampling [13]. Our data are consistent with studies showing that viral shedding from persons infected with SARS-CoV-2 peaks early in the course of infection [25,26] and that environmental contamination with SARS-CoV-2 is more likely when patient viral loads are at their highest [1]. Taken together, our data suggest that surface contamination with SARS-CoV-2 occurred through direct contamination with respiratory fluids following close, prolonged contact with sick persons early in their course of illness, particularly in the case of pillows and nightstands.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are congruent with a recent systematic review of higher quality studies (Byambasuren et al 2020) which used a fixed effect meta-analysis and found asymptomatic cases represented only 17% (95% CI 14% to 20%) of COVID-19 cases. A recent study of household transmission where a comprehensive capture of symptoms was done with use of a daily symptom monitoring tool, review of classic and non-classic symptoms plus initially daily RT-PCR testing, found 100% (12/12) of COVID-19 patients were symptomatic and is very consistent with our data (Lewis et al 2021). Our results are not congruent with earlier studies suggesting as many 40-45% of patients with COVID-19 are asymptomatic (Oran and Topol 2020) but much of the early literature was based on rapid and incomplete cross-sectional studies which were likely subject to significant bias.…”
Section: Discussionsupporting
confidence: 91%
“…Graphic presentation of the results could be standardised. We found the reporting of the evolution of transmission in the study by Lewis et al 24 . particularly helpful and clear.…”
Section: Research Recommendationsmentioning
confidence: 57%